2009
DOI: 10.1111/j.1600-0714.2009.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunoprofile of odontogenic keratocyst (keratocystic odontogenic tumor) that includes expression of PTCH, SMO, GLI‐1 and bcl‐2 is similar to ameloblastoma but different from odontogenic cysts

Abstract: The present results of the immunoprofile of OKCs (that includes the expression of the SHH-related proteins and the SHH-induced bcl-2 oncoprotein) further support the notion of OKC having a neoplastic nature. As OKCs vary considerably in their biologic behavior, it is suggested that the quality and quantity of interactions between the SHH and other cell cycle regulatory pathways are likely to work synergistically to define the individual phenotype and corresponding biological behavior of this lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 36 publications
5
37
0
1
Order By: Relevance
“…Second, recent laboratory research has suggested that a knowledge of the molecular and genetic alterations associated with KCOTs may predict individual biological behavior [10]. Vered et al [5] suggest that the immuneprofile of Sonic hedgehog (SHH)-related proteins and the SHH-induced bcl-2 oncoprotein may be able to define the individual KCOT phenotype and biologic behavior. These authors reviewed the current literature regarding possible future molecular oriented treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, recent laboratory research has suggested that a knowledge of the molecular and genetic alterations associated with KCOTs may predict individual biological behavior [10]. Vered et al [5] suggest that the immuneprofile of Sonic hedgehog (SHH)-related proteins and the SHH-induced bcl-2 oncoprotein may be able to define the individual KCOT phenotype and biologic behavior. These authors reviewed the current literature regarding possible future molecular oriented treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their benign classification, molecular analysis of the expression of PTCH, SMO, GlI-1 and bcl-2 in KCOT shows a profile similar to ameloblastoma rather than other odontogenic cysts [5]. In 1994 Jackson et al [6] reported 2 cases of OKC which invaded and penetrated the skull base and led to the death of one of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Discussion of this issue is not a subject of this review, but suggestions that reduced PTCH protein expression may be a marker for OKC, may provide evidence of neoplastic origin, or may distinguish syndromic from non-syndromic cysts have not been borne out. Immunohistochemical studies have shown that PTCH protein expression is similar in OKC, cystic ameloblastomas and other types of odontogenic cysts [27]. There is some evidence emerging that anti-apoptotic markers, including bcl-2 and BAX, may be specifically increased in OKC, but this needs confirmation and its diagnostic value has not been considered [27,28].…”
Section: Neoplastic Odontogenic Epitheliummentioning
confidence: 99%
“…Immunohistochemical studies have shown that PTCH protein expression is similar in OKC, cystic ameloblastomas and other types of odontogenic cysts [27]. There is some evidence emerging that anti-apoptotic markers, including bcl-2 and BAX, may be specifically increased in OKC, but this needs confirmation and its diagnostic value has not been considered [27,28].…”
Section: Neoplastic Odontogenic Epitheliummentioning
confidence: 99%
“…It is considered that the main cause for the origin of this lesion is a lack of regulation and a mutation in the PTCH gene 13 .…”
Section: Epidemiology and Etiopathogenesismentioning
confidence: 99%